2021
DOI: 10.1371/journal.pone.0244780
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the public response: Knowledge, attitude and practice of the public in mitigating the pandemic in Addis Ababa, Ethiopia

Abstract: Background The COVID-19 pandemic is impacting the global community in many ways. Combating the COVID-19 pandemic requires a coordinated effort through engaging public and service providers in preventive measures. The government of Ethiopia had already announced prevention guidelines for the public. However, there is a scarcity of evidence-based data on the public knowledge, attitude, and practice (KAP) and response of the service providers regarding COVID-19. Objective This study aimed to assess the public K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
53
8
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 24 publications
(44 reference statements)
23
53
8
11
Order By: Relevance
“…Moreover, higher knowledge scores were significantly associated with the positive attitude that COVID-19 will be successfully controlled. This finding is consistent with those of previous studies conducted in China [ 20 , 46 ], Malaysia [ 21 ], and other studies [ 48 , 50 ]. These findings imply that improving knowledge regarding COVID-19 can affect the attitude toward it and vice versa.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, higher knowledge scores were significantly associated with the positive attitude that COVID-19 will be successfully controlled. This finding is consistent with those of previous studies conducted in China [ 20 , 46 ], Malaysia [ 21 ], and other studies [ 48 , 50 ]. These findings imply that improving knowledge regarding COVID-19 can affect the attitude toward it and vice versa.…”
Section: Discussionsupporting
confidence: 94%
“…More than 90% of participants agreed that COVID-19 will be successfully controlled and believed that Indonesia can win against COVID-19. These results are similar to those of previous studies conducted in Indonesia [ 23 ] and elsewhere [ 26 , 42 , 48 , 49 , 50 ]. These results indicated that although COVID-19 has spread worldwide, most people had an optimistic attitude; they believed that the COVID-19 pandemic will end and that their countries will win against this pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…Results show that 48.19% ( n = 332) of the population had adequate knowledge of the nature, transmission, risk groups and precautionary measures of COVID-19. This rate of adequate knowledge is lower as reported in a Pakistani study (64.8%) ( 30 ), a Malaysian study (80.5%) ( 31 ) and a Chinese study (90%) ( 23 ) while higher than a Ethiopian study (36.7%) ( 12 ). However, this is in agreement with the findings of Abdelhafiz et al, who reported Egyptians had average (16.39 ± 2.63, range: 7–22) knowledge regarding COVID-19 ( 22 ).…”
Section: Discussionmentioning
confidence: 54%
“…People may not have access to regular and reliable sources of disease etiology information in the context of LMICs, leaving them ill-equipped to minimize the risk of infection in emerging outbreaks (8)(9)(10). Concerns have arisen about the possibility of obstructing public health communication due to misinformation (11)(12)(13). As WHO Director-General Dr. Tedros Adhanom Ghebreyesus said, "we're not just fighting an epidemic; we're fighting an infodemic" (14).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it was lower than 60.8% from Cameroon (32), 65% from South Wollo (23), and 59.8% from Addis Ababa (33). This could be related to the difference in the cut-values, i.e., this study used 75% cut of point to categorize prevention practice while former studies used 80% and above.…”
Section: Discussionmentioning
confidence: 74%